Legal regulation of waste management in Algeria - Cherif Hania (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2020)
Waste is one of the most important issues on one hand, and the most dangerous, on the other, because its danger lies in environmental problems due to the increase of population. Therefore, an increase in consumption resulting from household waste is due to the lack of culture in the community and awareness about the risk of waste to the environment as well as the lack of rigor in the application of legal texts. As to the importance of environmental, economic and social benefits through the recycling of waste and its utilization in several other areas. The direction towards optimal and better governance by the State allows us to achieve protection of the environment, since the State seeks to Environmental protection in the framework of sustainable development. From the legal point of view, the Algerian legislator regulated domestic waste through Law No. 03-10 of 20 July 2003 on the protection of the environment in the context of sustainable development and Law No. 01-19 of 12 December 2001 on the management, control and removal of wastes, Executive Decree No. 02-175 Of 20 May which includes the establishment, organization and operation of the National Agency for Waste, Law 11.10 on Municipalities and Law No. 12-07 on the State